O retorno à norma: o alcoolismo como produto da vida cotidiana - Francisco, Vinícius Nascimento (2015)
This study aims to analyze a particular course of action understood as a disease by the medical science and an offense to the structuring of processes ordered face-to-face interaction in everyday life. Alcoholism was selected for the theoretical and empirical object as the social experiences of members of self-help groups that acquired a social significance in recent decades: the "Alcoholics Anonymous" AA. The AA is a physical space that apprehends alcoholism as a matter related to the daily lives of men and women stigmatized as drunk. The AA members strive gradually in overlay alcoholism with a language related to the reorganization of their everyday lives. . In the first instance, we address the intrinsic relationship between the systemic world of science, its way to make sense to alcoholism (rational construction of the disease conception) and their acceptance of disability on other approaches to the problem of excessive alcohol consumption in social life. In a second step, we show the historical and political development of the United States and favorable social conditions for the emergence of a movement that understands alcoholism from the public discussion on the way to the common good of society. On a third occasion, we study the social experiences of AA members and the construction of belief in alcoholism within the group as a spring abnormality of disruption of the privacy of its visitors. We understand therefore that alcoholism for AA membership is a fact that hindered his performances in everyday social relations - and will continue blocking if nothing is done to understand the abnormality of those who constantly drink in everyday life. The work was based on qualitative methodologies such as case study, having been selected for the AA your research, semi-structured interviews with the group members, systematic observation of AA meetings and document analysis used by its frequenters